Preparation and Antimicrobial Activity Analysis of Organic Soap Bar Containing Gnetum gnemon Peel Extract - Sri Handayani; Indyah Sulistyo Arty; Cornelia Budimarwanti; Karim Theresih; Evy Yulianti; Melati Khairuddean (Universitas Jenderal Soedirman, 2021)
Melinjo (Gnetum gnemon L.) peel has been known as antioxidant, antibacterial, and antifungal, but not yet used as cosmetic ingredients or drugs optimally. This research focuses on the production of organic soap bars from melinjo peel extract, the quality testing, and antimicrobial analysis against selected microbes. The soap making process was done by the saponification reaction between the mixture of palm oil and coconut oil with sodium hydroxide through cold and hot processes. Distilled water and ethanol were used as solvents for melinjo peel extraction. The quality test was done by determining insoluble fraction in ethanol, free alkali, and unsaponified fatty matter. An antimicrobial activity test was conducted using the Kirby-Bauer diffusion method. The result shows that the quality test fit with INS 2016 for all the criteria except for unsaponified fatty acid in the cold process soap bar. Inhibition zone of organic soap bar sequentially decreased against the growth of Tricophytone mentagrophytes, Staphylococcus aureus, and Staphylococcus epidermidis. Therefore, the organic soap bar with melinjo peel extract shows a good potential to be used as an antimicrobial soap.